Effect of sucker pruning on sago palm (Mextroxylon sago Rottb.) growth performance - Howell, Peter Stanley (2017)
Sago palm (Metroxylon sagu Rottb.) had been commercially cultivated in Sarawak for both export and domestic consumption. Sarawak is the world main exporter for sago starch which is one of the state important agriculture commodities. Currently, the world demand for sago starch had increased tremendously, however the supply is insufficient. Inconsistent harvesting with lengthy harvesting interval had been known to affect the supply of sago logs. Lack of knowledge for systematic sago sucker management is also one of the reasons that hinder the palm growth performance resulting in low and inconsistent sago logs supply to the mills. The objectives of this study were to determine the effect of sucker pruning on the sago mother palm and succession sucker growth performance as well as the allocation of above ground biomass of the sago cluster. The study was conducted on an existing sucker pruning trial in Sungai Talau Research Station, CRAUN Research, Dalat, Sarawak, which was established in 2007 on a deep peat area. The study consisted of five sucker pruning treatments that were carried out three times each year. Number of trunking palm, trunk or palm base girth circumference, trunk height and frond count were recorded yearly to determine the growth performance for both mother palms and succession suckers. The cluster’s fresh weight was determined by felling every single palm within the cluster, separated into different vegetative parts and weighed. Adequate amounts of samples were collected and dried using drying oven to estimate the above ground biomass ratio allocated between the different vegetative parts. Results showed significant difference for growth performance of both mother palms and succession suckers and also on the allocation of biomass within the sago cluster when sucker pruning was done. Pruned sago clusters with regulated number of palms at certain period of time exhibited higher formation of trunking palms with broader base girth and taller trunks. The biomass ratio allocation pattern was found to be higher in trunks and frond formation followed by leaves production. Sucker pruning activity may have minimised competition for nutrient, sunlight and growing space between palms within the sago cluster. Less congested cluster with evenly spread palms enabled each individual growing palm to receive optimum nutrient, sunlight and space for optimum growth performance. Congested sago cluster were observed to have tensed competition for growth factors and concentrated more on fronds and leaves production instead of trunk. The outcomes of the study showed that sago clusters under T4 produced higher number of taller and broader trunking palms for both mother palm and succession suckers with high biomass allocation for trunk formation. Sucker pruning system, initiated after three years of field planting, conducted three times a year with one succession sucker to be retained every 18 months interval to be recommended to improved sago growth performance and sustainability of yield production. However, study on the nutrient uptake, starch yield and growth performance for sago palm cultivated on different type of soil in response to sucker pruning should be initiated.